Les CARACTERES DES FRANCAIS DANS LE SPOT PUBLICITAIRE FRANÇAIS ET SON ACCORD AVEC L’EDUCATION DU CARACTERE A L’UNIVERSITE D’ETAT SEMARANG - Amalia, Dini; Handayani, Sri; Purwani, Neli (Didacticofrancia: Journal Didactique du FLE, 2016)
The purpose of this study was to describe the French TV ads that contains a description ofvalue the characters, and its compatibility with character education in Semarang State University. This study using qualitative descriptive approach. The data in this study are the characteristics of the French in French-language TV ads which are downloaded from the site www.youtube.com. Data collection techniques in this study are techniques of documentation, see,and record. Data analysis technique used is the technique analysis of the message content. Theresults shows that in six French TV ads, there are fourteen characters and habits of the French:polite, willing to help, attentive and loving, vigorously, intelligent, individualistic, adventurous, conscientious or not careless, friendly, disciplined, obedient to the rules, romantic, custombises, and fashionable. Of the French characters and habits of the French appearing, there areeight in accordance with the value of character education in Semarang State University. Thecharacters that correspond to the value are: smart, responsibility, caring, tolerant, democratic,patriotism, firm, and politeness.